The Latest Treatment Interventions Improving Mental Health Outcomes for Women, Following Gender-Based Violence in Low-and-Middle-Income Countries: A Mini Review - St. John, Lily; Walmsley, Rebecca (Frontiers in Global Women's Health, 2021)
Gender-based violence (GBV), specifically violence against women, is a worldwide pandemic. Prevalence is further escalated in low-and-middle-income countries and in humanitarian crises. Survivors are left with a combination of post-traumatic stress disorder, depression and anxiety. These mental health disorders lead to further morbidity and mortality. Despite its high prevalence and co-morbidities, gender disparities and mental health stigma globally lead to few interventions developed for this population. The aim of this review is to highlight the mental health interventions developed in the past five years, for women following GBV in low-and-middle-income countries. It aims to discuss their efficacy and controversies when implemented into healthcare systems, understand the gaps that remain in the field and suggest future research developments. A thorough literature search revealed 16 new interventions available for improving mental health outcomes for women following GBV in low-and-middle-income countries. Following an in-depth evaluation of the papers, one intervention was successful in effectively implementing treatment into healthcare systems – ‘PM+’. However, it proved only to be effective in the short term. Further research must be done for improving long-term mental health outcomes. Results demonstrated poor follow-up for women engaging in group therapy. The review also highlights community workers were used in service delivery to reduce barriers accessing care. No interventions proved effective in humanitarian crises, despite GBV escalated in these settings. There are very few interventions available in comparison to the prevalence of this global health issue. Therefore, this review encourages further research and improvements in mental healthcare interventions following GBV.